A Comprehensive Analysis of the Protocols of Wireless Sensor Network (WSN) - Ms. P. Sangeetha; Dr. D. Kavitha (The Bioscan, 2025)
The Wireless Sensor Network (WSN) has been widely used in other technologies like the Internet of Things, artificial intelligence, etc. since it is dependable. There have been several uses that are related. The WSN is becoming more dependable and well-liked as one of the apps on the network. WSN is regarded as the most important technology of the twenty-first century and is essential to connecting the rational information world with the existing physical world. Numerous sensor nodes in a Wireless Sensor Network (WSN) have limited power, storage, and processing ability. The performance of these systems can be enhanced by employing clustering. In Wireless Sensor Networks (WSN), the clustering methods concentrated mainly on power consumption, which may cause increased overhead. More energy is consumed when the cluster head periodically sends the data, leading to cluster head re-election. Due to the nonuniform node distribution, the energy consumption among nodes is more imbalanced in cluster-based WSNs. The key challenge in WSN is to schedule the node activities for data transmission by maintaining energy consumption. This article explains the context of WSN and its recent research work, where the recent issue is identified and discussed. Keywords Energy consumption, sensor node, power consumption, clustering, secure, and network lifetime.